Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode CAMEL (Capital, Asset, Management, Earning, Liquidity) Pada Bank Aceh Syariah Periode 2019-2022) - Himma Arasy Attamimi; Rizqi , Alfiana; Windaningrum, Windaningrum (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
The study aims to determine the health status of the Aceh Sharia Bank by assessing whether the bank is in a healthy, sufficiently healthy, unhealthy, and inadequate condition. This research uses the CAMEL method (Capital, Asset, Management, Earning, Liquidity) with the financial ratio CAR, NPF, BOPO, NPM, ROA, ROE, FDR. The data used in this research is obtained from the data of the Financial Report of the Annual Publication of the Bank of Aceh Shariah period 2019-2022. This type of research is descriptive research with a quantitative approach. For that, the data source required in this study is secondary data which is the financial report of the bank of Aceh shariah during the 2019-2022 period. The result of the analysis is that the Capital Satisfaction Ratio (Capital) analyzed with KPMM showed good progress and entered the rank very healthy. Next, the Quality Ratio of Productive Assets (Assets) through the NPF analysis with stagnant results or no major changes, but the ranking is still in the very healthy rank. Then the Management Quality ratio (Management) with the BOPO and NPM analysis. The BOPo ratio in the bank aceh shariah is categorized very well and is in the rank 1. The same with the NPM ratio is categorised very good and is at the rank 1 because the overall score is above 100%. Next the Earning Ratio through ROA and ROE. The ROA analysis shows a decrease from four years. While the ROE analysis shows decreases every year. Then the last Liquidity Ratio showed up and down but still in the very healthy ranking category